Parkinson's disease biomarkers: perspective from the NINDS Parkinson's Disease Biomarkers Program. (June 2017) - Gwinn, Katrina; David, Karen K; Swanson-Fischer, Christine; Albin, Roger; Hillaire-Clarke, Coryse St; Sieber, Beth-Anne; Lungu, Codrin; Bowman, F DuBois; Alcalay, Roy N; Babcock, Debra; Dawson, Ted M; Dewey, Richard B; et al.
Biomarkers for Parkinson's disease (PD) diagnosis, prognostication and clinical trial cohort selection are an urgent need. While many promising markers have been discovered through the National Institute of Neurological Disorders and Stroke Parkinson's Disease Biomarker Program (PDBP) and other mechanisms, no single PD marker or set of markers are ready for clinical use. Here we discuss the current state of biomarker discovery for platforms relevant to PDBP. We discuss the role of the PDBP in PD biomarker identification and present guidelines to facilitate their development. These guidelines include: harmonizing procedures for biofluid acquisition and clinical assessments, replication of the most promising biomarkers, support and encouragement of publications that report negative findings, longitudinal follow-up of current cohorts including the PDBP, testing of wearable technologies to capture readouts between study visits and development of recently diagnosed ( de novo ) cohorts to foster identification of the earliest markers of disease onset.